A comparative study related to effect of Human resource information systems on implementation of HRA system in India and Kurdistan region of Iraq. - SURARCHITH, DR. NAVULUR KRISHNA; SHRIVASTAVA, DR. ROOPAL (The journal of contemporary issues in business and government, 2021)
The present research concentrated on acknowledging practices related to Human Resource Accounting in India and Kurdistan region under process oriented industry. The organizations selected for the present research are Al Mansoori Petroleum Services Ltd., Kurdistan Region of Iraq and Cement Corporation of India Ltd., India. Observations made by the researcher were to check the effect of Human Resource Information System on implementing Human Resource Accounting systems. The data was collected by constructing a questionnaire and distributed to respondents in two organizations. The study was conducted with a sample size 570 (386 from Cement Corporation Limited and 184 from Al Mansoori Petroleum Services Limited) have been considered for general evaluation. 46 (26 from CCI and 20 from AMPS) from the above lot has been taken separately confined only to the employees of HR & Finance departments considered for the evaluation. The results depict that Human Resource Information System has a significant influence on implementing HRA System.